PERSPEKTIF HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI MENGGUNAKAN POTONGAN HARGA (DISKON) DENGAN BERJANGKA WAKTU - Winda Pristiwanti; Danang Setiawan (Jurnal At-Tabayyun, 2021)
This research examines the views of Islamic law regarding buying and selling practices that involve discounts or fixing the time of purchase. Discounts with a certain period of time is a common marketing strategy in the business world. However, in the context of Islamic law, this practice raises several problems related to its legitimacy, justice and adherence to Islamic principles. This essay tries to explore the perspective of Islamic law regarding the practice of buying and selling through timely discounts and provides advice for Muslim entrepreneurs regarding this phenomenon.